PENGARUH KEMAMPUAN LITERASI MEMBACA TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR - Saeful Amri; Eliya Rochmah (Universitas Pendidikan Indonesia, 2021)
The background of this research is the low of reading literacy skills in SDN Pegagan. The low of reading skills is thought to have an effect on student achievement as well. This is indicated by the results of student achievement that are still low. The purposes of this research are to (1) Know the reading literacy skills of student (2) Know the level of student achievement, and (3) Know the influence of reading literacy skills on student achievement in SDN Pegagan. The study design used quantitative survey research with a sample of 88 students in SDN 1, 2, and 3 Pegagan. Data analysis used simple linear regression test. The results showed that (1) the reading literacy skills of students was quite sufficient at 67.53%, (2) The students' learning achievement was classified as very good at 81%, and (3) There was a significant influence of 5.4% between reading literacy skills and student achievement learning.